P428 Pharmacist-led proactive therapeutic drug monitoring with infliximab (PROXIMO): Utility of and cost-saving associated with the use of a rapid assay for assessing drug level. (16th January 2018) - Rentsch, C; Sparrow, M; Ward, M; Taylor, K; Friedman, A; Luber, R; Su, H; Hopkins, R; Head-on, B; Dooley, M; Gibson, P
Abstract: Background: Optimised infliximab (IFX) dosing in patients with IBD is required to achieve therapeutic drug levels. Rapid assays enable same-day dose adjustment with the potential benefits of faster dose-optimisation, improved clinical outcomes, and reduced risks associated with high levels. To compare a rapid IFX assay to standard ELISA, assess effect of proactive dose adjustment on disease activity, and compare cost-effectiveness of this approach to standard therapy. Methods: In a 12-month prospective single-centre study of adult IBD patients receiving 8-weekly 5 mg/kg maintenance IFX therapy, trough IFX concentrations were assessed via the rapid test (Bühlmann) before each infusion with immediate dose adjustment targeting 3–7 μg/ml. Disease activity was assessed using the Harvey Bradshaw index for Crohn's disease and simple clinical colitis activity index for ulcerative colitis, CRP (<3 mg/l remission) and faecal calprotectin (<150 μg/g, remission). The rapid test was compared with ELISA (Matriks). Cost-analysis used retail prices of IFX and the rapid assay. Results: Thirty-five patients have completed 6 months, 19 of whom completed 12 months. Agreement between the rapid assay and ELISA was very good with Pearson r = 0.70 ( p < 0.0001) and Bland Altman average bias = 0.36 [95% CI −5.39 to 4.6] μg/ml across 205 paired samples. Overall, therapeutic levels were achieved after 3 infusions (Figure 1). At study entry, 51% dose reduced and 26% escalated. By 6 and 12 months, levels in 17 of 35 (49%) and 11 of 19 (58%) were therapeutic. Greater than 50% of patients received <5 mg/kg during optimisation. Rates of remission on clinical criteria, CRP or calprotectin were unchanged with dose reduction ( p = 0.37), despite temporary sub therapeutic levels on next testing in 3 patients. The dose-intensification regimen used achieved therapeutic levels in 50% and 100% at 6 and 12 months, and per-encounter remission rates increased by 27% ( p = 0.031) and 21% ( p = 0.125) for clinical, and 13% and 5% for biochemical (CRP) remission ( p = 0.69 for both). Calprotectin did not change ( p = 0.5). The rapid-test strategy saved AUD 214/patient/year compared with standard care. Conclusions: The rapid test is accurate and its application in the setting of maintenance therapy led to dose adjustment in three of four patients and higher rates of therapeutic levels, implying standard weight-based dosing is inadequate. Dose-reduction did not carry risk of relapse. This rapid-test strategy has the potential to reduce patient risks and improve patient outcomes without negative costs implications.